Analisis Pengaruh Kinerja Keuangan dalam Memprediksi Pertumbuhan Laba - ., R. Adisetiawan (Universitas Brawijaya, Indonesia, 2012)
This study was conducted to examine the effect of variables Working Capital to Total Assets(WCTA), Current Liabilities To Inventory (CLI), Operating Income to Total Assets (OITL), Total AssetsTurnover (TAT), Net Profit Margin (NPM) and Gross Profit Margin (GPM) on the growth of earnings. Dataobtained by the method of purposive sampling criteria: (1) companies incorporated in LQ45 2008-2010period, (2) companies that are engaged in services, (3) and during the study period these companies do notgenerate profits the negative. The analysis showed that the data used in this study have met the classicalassumptions, which include: no symptoms of multicollinearity, there is no autocorrelation, no symptomsoccur heteroskedastisitas, and normally distributed data. From the results of regression analysis showedthat the variable Operating Income to Total Assets (OITL) and Net Profit Margin (NPM) partially significanteffect on earnings growth. While the variables Working Capital to Total Assets (WCTA), CurrentLiabilities To Inventory (CLI), Total Assets Turnover (TAT), and Gross Profit Margin (GPM) no significanteffect on earnings growth. The six variables used in this study (WCTA, CLI, OITL, TAT, NPM and GPM)simultaneously no significant effect on earnings growth, with the predictive capabilities of the six variablesof 4.4%.